DEVELOPMENT OF MATHEMATICS LEARNING MEDIA USING KAHOOT APPLICATION - Afra Yunisa Rahmi; Rezi Ariawan (Jurnal Prinsip Pendidikan Matematika, 2022)
Learning in the Industrial Age 4.0 is currently expected to produce quality human resources to face these global developments and competition. The implication of this is that it is expected that teachers will be creative and active in designing and conducting creative and innovative learning. Based on this, the researcher aims to produce mathematics learning media using the Kahoot application, tested for validity. This research was conducted in the even semester of the 2020/2021 academic year. The type of research used in this research is research and development with ADDIE development design. The validation sheet is a data collection instrument used in this study. The non-test technique was used to obtain data from this study by asking for responses from 4 expert validators. The data obtained were analyzed using quantitative descriptive techniques. Based on the analysis of the data obtained information that the resulting mathematics learning media using the Kahoot application that has been tested for validity with very valid criteria or with a percentage of 82.78%.